Pengaruh Model Problem Based Learning berbantuan Game Ular Tangga Digital terhadap Hasil Belajar Pendidikan Pancasila Materi Hak dan Kewajiban - Asih, Mifta Romadhani; Susiloningsih, Wahyu (Universitas Muhammadiyah Magelang, 2026)
This study aims to determine the effect of the use of the Problem Based Learning model assisted by the digital snakes and ladders game on the learning outcomes of Pancasila Education on the rights and obligations of third-grade elementary school students. The background of the study is based on the low student learning outcomes caused by the use of conventional learning methods. The Problem Based Learning model encourages students to learn actively through solving problems related to real life, while the digital snakes and ladders game acts as an interesting and interactive learning medium to deepen students' understanding. This study uses a quantitative approach with a quasi-experimental method through a nonequivalent control group design involving a pre-test and post-test. The research subjects were 48 third-grade students of UPT SDN 145 Gresik, consisting of 24 students in the experimental class and 24 students in the control class. The data collection technique used a learning outcome test that had been tested for validity and reliability, while data analysis was carried out through normality tests, homogeneity tests, and hypothesis tests using the T-test. The results of the Independent Samples Test showed a significant difference between the post-test results of the experimental class and the control class. Thus, it can be concluded that the use of the Problem Based Learning model assisted by the digital snakes and ladders game has a significant effect on the learning outcomes of Pancasila Education for third grade elementary school students.